Integrated-Skills and Segregated-skills approaches in the teaching of Speaking for EFL Learners - ARAB , Ouided; Belouahem, Riad (Journal of Human Sciences, 2022)
The current study aims at exploring whether teachers follow the integrated-skills or the segregated-skills approach in the process of teaching the speaking skill in Oral Expression module. It also attempts to examine the learning/teaching process of the speaking skill and its integration with the other macro and micro skills. The study takes the case of first year students, at the Department of Arts and the English Language, Frères Mentouri Constantine 1 University. To achieve this aim, two questionnaires are adopted. The first is administered to one hundred twenty (120) first-year students, and a second one is assigned to twenty-one (21) teachers of Oral Expression. The obtained data confirmed that the macro and micro skills were combined to speaking with varying degrees, but they were arbitrarily integrated; that is why the integrated approach was not properly applied.